Blocking Entry of Hepatitis B and D Viruses to Hepatocytes as a Novel Immunotherapy for Treating Chronic Infections. (29th January 2020) - Maravelia, Panagiota; Frelin, Lars; Ni, Yi; Caro Pérez, Noelia; Ahlén, Gustaf; Jagya, Neetu; Verch, Georg; Verhoye, Lieven; Pater, Lena; Johansson, Magnus; Pasetto, Anna; Meuleman, Philip; et al.
Abstract: Background: Chronic hepatitis B and D virus (HBV/HDV) infections can cause cancer. Current HBV therapy using nucleoside analogues (NAs) is life-long and reduces but does not eliminate the risk of cancer. A hallmark of chronic hepatitis B is a dysfunctional HBV-specific T-cell response. We therefore designed an immunotherapy driven by naive healthy T cells specific for the HDV antigen (HDAg) to bypass the need for HBV-specific T cells in order to prime PreS1-specific T cells and PreS1 antibodies blocking HBV entry. Methods: Ten combinations of PreS1 and/or HDAg sequences were evaluated for induction of PreS1 antibodies and HBV- and HDV-specific T cells in vitro and in vivo. Neutralization of HBV by PreS1-specific murine and rabbit antibodies was evaluated in cell culture, and rabbit anti-PreS1 were tested for neutralization of HBV in mice repopulated with human hepatocytes. Results: The best vaccine candidate induced T cells to PreS1 and HDAg, and PreS1 antibodies blocking HBV entry in vitro. Importantly, adoptive transfer of PreS1 antibodies prevented, or modulated, HBV infection after a subsequent challenge in humanized mice. Conclusions: We here describe a novel immunotherapy for chronic HBV/HDV that targets viral entry to complement NAs and coming therapies inhibiting viral maturation. Abstract : The paper shows a completely new immunotherapy for chronic hepatitis B and potentially also hepatitis D. The immunotherapy induced neutralizing antibodies and T cells targeting both HBV and HDV. Importantly, the induced antibodies neutralized HBV in vitro and in vivo.